The joint ınvolvement pattern of granulomatous polangiitis changed? Multicenter study - Albayrak, Fatih; Oz, Burak; Yamancan, Guelsah; Kutlu, Nagehan Dik; Kudas, Ozlem; Coskun, Belkis Nihan; Kisacik, Bunyamin (Springer London Ltd, 2025)
ObjectivesGranulomatosis with polyangiitis (GPA) formerly Wegener's granulomatosis is a type of anti-neutrophil cytoplasm antibody (ANCA)-associated vasculitis (AAV) typically associated with necrotizing, granulomatous inflammation. Musculoskeletal manifestations have been described in 40-65% of patients. Arthritis usually occurs as large, single and asymmetric joint involvement, but rarely symmetrical small joint involvement may also occur. We present 56 cases whose initial presentation was mostly symmetrical and polyarthritis, which caused a significant diagnostic delay.MethodsFifty-six patients who presented with inflammatory arthritis in the last 3 years and were diagnosed with GPA as the final diagnosis were included in the study. One hundred patients, diagnosed as GPA, with a similar age-sex ratio of 1:2 from each center were included as the control group.ResultsPolyarthritis was present in 32 (57.1%) patients, oligoarthritis was present in 21 (37.5%) patients and monoarthritis was present in three (5.4%) patients. The most commonly involved joints were wrist in 37 (66.1%) patients, ankle in 30 (53.6%) patients, metacarpophalangeal joint in 25 (44.6%) patients, knee in 23 (41.1%) patients, shoulder in 22 (39.3%) patients, elbow in 18 (33.9%) patients, hip in three (5.4%) patients and temporomandibular joint in one (1.8%) patient.ConclusionAlthough the typical joint involvement of GPA has been reported as lower extremity monoarthritis-oligoarthritis in the large series, our study demonstrates that symmetry and polyarthritis may be a more frequent presenting feature than previously recognized. It is important that joint involvement patterns in larger GPA series are reported in detail in order to compare our results.Key Points:center dot This study is important because it shows in detail which joints are affected and the pattern of involvement in cases of GPA with arthritis.center dot Diagnosis may be delayed in cases of GPA presenting with arthritis.center dot Symmetric, and polyarthritis involvement may be seen significantly more frequently in GPA cases.ConclusionAlthough the typical joint involvement of GPA has been reported as lower extremity monoarthritis-oligoarthritis in the large series, our study demonstrates that symmetry and polyarthritis may be a more frequent presenting feature than previously recognized. It is important that joint involvement patterns in larger GPA series are reported in detail in order to compare our results.Key Points:center dot This study is important because it shows in detail which joints are affected and the pattern of involvement in cases of GPA with arthritis.center dot Diagnosis may be delayed in cases of GPA presenting with arthritis.center dot Symmetric, and polyarthritis involvement may be seen significantly more frequently in GPA cases.
Keywords: Granulomatosis with polyangiitis; Polyarthritis; Vasculitis; Wegener's